A Classic Case of Madura foot in South Rajasthan (Indian Journal of Case Reports, 2024)
Madura foot, known for its rarity and tendency to recur, is a chronic granulomatous disease of fungal and bacterial origins. Eumycetoma, the fungal variant, involves deeper tissues at a late stage and it is function-sparing even during the advanced stage of the disease. Clinically, diagnostic black grains, imaging, and histopathology play a critical role in clinching the diagnosis of this deep infestation. Meticulous wide surgical excision, serial debridements, and long-term antifungals provide the mainstay for the treatment of eumycetoma. We report an under-treated case of recurrence of eumycetoma in a young rural farmer who was suffering from eumycetoma for about a year. Initial sub-optimal management resulted in the disease festering over a long period of time. Most of the left midfoot was involved on the presentation without any bony involvement. Even after exhibiting all classical signs of eumycetoma at various points in time, our patient was under-treated highlighting the need for increased awareness, early diagnosis, and better long-term management of this disease.